1984
DOI: 10.1111/j.1442-9993.1984.tb01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed characteristics and regeneration of some species in invaded coastal communities

Abstract: The seed production, germination and regeneration characteristics of two native species (Acacia Iongifolia var. sophorae and Banksia integrifolia) and two invasive subspecies (Chrysanthemoides monilifera ssp. monilifera and ssp. rotundata) were compared.C. monilifera ssp. rotundata was similar in seed characteristics and regeneration to B. integrifolia in that: (1) seed production was over an extended period each year; (2) seed longevity was low (0-2% viable after burial for 3 years), but increased with depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 5 publications
3
52
0
Order By: Relevance
“…If these dispersed seeds in the upper layers were transient, then there must be both continual addition andloss (Keeley 1977),includingpredation (Kjellson 1985;Wellington & Noble 1985), germination followed by unsuccessful establishment, and loss of viability with time (Schafer & Chilcote 1970;Weiss 1984). At some study sites unsuccessful establishment following germination has been observed in bracken stands adjacent to forest, where seedlings of forest species have been seen to survive during winter, but die the following summer.…”
Section: Discussionmentioning
confidence: 99%
“…If these dispersed seeds in the upper layers were transient, then there must be both continual addition andloss (Keeley 1977),includingpredation (Kjellson 1985;Wellington & Noble 1985), germination followed by unsuccessful establishment, and loss of viability with time (Schafer & Chilcote 1970;Weiss 1984). At some study sites unsuccessful establishment following germination has been observed in bracken stands adjacent to forest, where seedlings of forest species have been seen to survive during winter, but die the following summer.…”
Section: Discussionmentioning
confidence: 99%
“…Acacia spp. Weiss 1984;Auld 1986;Keith et al 2002). Alternatively, some limited on-going establishment could be possible if seedlings were able to tolerate the existing cover of shrubs, herbs and grasses, or if they emerged into gaps caused by mortality of adult trees or shrubs as suggested for several Leucopogon species in the region (Ooi et al 2006b).…”
Section: Discussionmentioning
confidence: 93%
“…This is logical considering the persistent growth, reproduction and hence metabolism of C. monilifera spp. rotundata throughout the year (Weiss 1984). However the A. longifolia var.…”
Section: Discussionmentioning
confidence: 97%
“…All of the test species involved in the present study are likely to experience increased germination rates from winter to spring in accordance with the increasing temperatures and rainfall. This is particularly the case for B. integrifolia which seeds during winter and spring and has low seed bank viability (Weiss 1984). I. nodosa typically seeds in summer, although may seed throughout the year and is expected to have low soil seed bank longevity (Ens personal observation).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation